Implementation of dynamic misalignments and luminosity stabilization - Hendrickson, L; Himel, T; Raubenheimer, T; Seryi, A; Tenenbaum, P; Woodley, M (2003)
To fully characterize the luminosity performance of a linear collider, it is important to simulate the effects of ground motion as well as the beam-beam feedback and other stabilization systems planned to compensate for that motion. The linear collider simulation codes have recently been extended to include both ground motion models and stabilization systems to support the work of the International Linear Collider Technical Review Committee (TRC). This paper discusses the implementation details and the optimization strategies for interpulse beam-beam feedback.